2011
DOI: 10.1039/c1cc12764k
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to design highly efficient porphyrin sensitizers for dye-sensitized solar cells

Abstract: We designed highly efficient porphyrin sensitizers with two phenyl groups at meso-positions of the macrocycle bearing two ortho-substituted long alkoxyl chains for dye-sensitized solar cells; the ortho-substituted devices exhibit significantly enhanced photovoltaic performances with the best porphyrin, LD14, showing J(SC) = 19.167 mA cm(-2), V(OC) = 0.736 V, FF = 0.711, and overall power conversion efficiency η = 10.17%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 256 publications
(187 citation statements)
references
References 23 publications
4
183
0
Order By: Relevance
“…The values of V OC of YD2-oC8 and YD30 were significantly greater than of V OC of YD2 because of the effect of the long alkoxyl chains attached at the ortho positions of the meso-phenyls. 5,17 The overall photovoltaic performances of the thin-film samples are consistent with those of the optimized devices; 5 the observed E-PL results measured for TiO 2 films of thickness ∼3 μm are utilized to rationalize the photovoltaic performances of porphyrin dyes in this series.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The values of V OC of YD2-oC8 and YD30 were significantly greater than of V OC of YD2 because of the effect of the long alkoxyl chains attached at the ortho positions of the meso-phenyls. 5,17 The overall photovoltaic performances of the thin-film samples are consistent with those of the optimized devices; 5 the observed E-PL results measured for TiO 2 films of thickness ∼3 μm are utilized to rationalize the photovoltaic performances of porphyrin dyes in this series.…”
Section: Resultsmentioning
confidence: 87%
“…These orthosubstituted devices outperformed their para-and metasubstituted counterparts because a substitution of the long alkoxyl groups at the ortho-position protects the porphyrin cores from dye aggregation and from forming a blocking layer on the TiO 2 surface. 5,17,18 Electroabsorption (E-A) and electrophotoluminescence (E-PL) spectra, i.e., plots of the change of an absorption spectrum and photoluminescence spectrum, respectively, induced with an electric field have been extensively used to examine electronic properties, such as electric-dipole moment and molecular polarizability, for organic and polymeric thin-film systems. 19−23 Several authors reported the effects of local electric fields on the optical properties of DSSC.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59] In our case, OD9 was co-sensitized with the new porphyrin dye LW24 (Scheme2). As an analogue of the porphyrin dye LD14, [60,61] the LW24 dye is functionalized with an electron-withdrawing BTD unit to extend the conjugation length in the p bridge for the same purpose of OD9. The BTD unit is inserted between the porphyrin core and the benzoic acid.…”
Section: à2mentioning
confidence: 99%
“…Recently, alternative dyes to ruthenium complexes have been reported in the literature. These dyes contain large π-π aromatic molecules such as metalloporphyrins (MPs), and they constitute an important class of sensitizers on TiO 2 [20][21][22][23][24][25][26]. The central metal in the dye is zinc.…”
Section: Introductionmentioning
confidence: 99%